A randomised controlled trial of integrated electrical stimulation and physiotherapy to improve mobility for people less than 6 months post stroke. (November 2015) - Wilkinson, Ingrid A.; Burridge, Jane; Strike, Paul; Taylor, Paul
Abstract Purpose: To investigate the feasibility of combining physiotherapy and functional electrical stimulation to improve gait post stroke. Methods: A parallel group partially single-blinded randomised clinical trial. Adults living at home, less than 6 months post stroke, were randomised to Group A (physiotherapy, n = 10) or Group B (physiotherapy and common peroneal nerve stimulation, n = 10). Assessments were conducted before randomisation (Week 1), after intervention (Week 8) and after 12 weeks follow-up (Week 20). Results: No between group differences were observed. There were statistically significant within group differences after the intervention period in both groups for walking speed and distance walked (without stimulation), Rivermead Mobility Index and Canadian Occupational Performance Measure, maintained at Week 20. There was statistically significant improvement in 10-m walking speed (Group B) when the stimulator was used at Week 8 (p = 0.03, median 0.04 m/s (8%)). Only Group B had statistically significant within group change in Rivermead Visual Gait Analysis (Week 8), maintained at Week 20. Conclusions: Integrating electrical stimulation and physiotherapy was feasible and improved walking speed. There was no evidence of a training effect compared with physiotherapy alone. One-hundred forty-four participants per group would produce an adequately powered study based on this protocol. Implications for Rehabilitation At the end of the intervention period participants using electrical stimulation to correct dropped foot walked faster. It was feasible for electrical stimulation to be combined with physiotherapy for people less than 6 months post stroke. A larger adequately powered study is required to establish whether there are training effects associated with use of stimulation in this population.